Scope and limits of the administrative act arbitrability - Bravo, Bárbara Magalhães (2019)
The material scope of arbitration in administrative matters has recently been considerably enlarged, especially in regards to the administrative act. It was recognized that the Arbitral Tribunal has the power to appreciate the legality of an administrative act. Traditionally, the legality of administrative acts was reserved for state courts. However, the legal incongruity was notorious. Article 180 (1) (c) of the Code of Procedure of the Administrative Courts (CPTA), 2002, provided that arbitral tribunals could enounce "matters relating to administrative acts that could be revoked without grounds for invalidity". We could diagnose two types of legal failures. First, within Administrative Law, it was incomprehensibly admissible to arbitrate the legality of administrative acts pertaining to the contractual sphere and exclude all others from the control of arbitration law. The other flaw suffered by the regime of arbitrability of administrative acts related to the possibility of arbitrability of tax acts3 and the imposition of strong limitations on the control of the legality of administrative acts in Administrative Law. The revision of the CPTA in 2015 implied a change in the legislative paradigm in the matter of administrative arbitration, providing for the possibility by the arbitral tribunals of assessing the legality of the administrative act, thus putting an end to a doctrinal dispute about the admissibility of the same. However, a literal interpretation of the precept would lead us to subsume within the jurisdiction of the arbitral tribunals the assessment of the legality of any administrative act. Considering the legislative scope of the legal prediction enunciated, the present work will have as its objective to answer three key questions. The first is to assess to what extent the arbitral tribunals may rule on the merit and legality of the administrative act. The second is to determine whether all administrative acts are arbitrable. The third concerns the search for a criterion of arbitrability of the administrative act, especially in matters related to legality.